Physicochemical Properties and Stability of Emulsions Containing Carotenoid-Rich Pumpkin Extract, Whey Protein Concentrate and Carboxymethylcellulose - Ibrahim, Nor Hayati; Yi, Tan Kang; Isa, Suaidah Mohd; Hadi, Nabilah Abdul; Ali , Asma’ (Jurnal Gizi dan Pangan, 2023)
A response surface methodology with a central composite design was employed to investigate the effects of Carotenoid-Rich Pumpkin Extract (CE), Whey Protein Concentrate (WPC), and Carboxymethyl Cellulose (CMC) on the physicochemical properties and stability of emulsions. The WPC-CMC synergism resulted in the formation of a thick layer around the droplets, thus improving the emulsion system. The optimum levels of CE, WPC, and CMC were determined to be 6.00, 2.00, and 0.87%, respectively, to provide the desired emulsion with a pH of 4.18, a carotenoid degradation stability index of 0.88, a peroxide formation stability index of 0.77, and an apparent viscosity of 0.61 Pa.s.